Impact of oil price changes and energy consumption on economic growth and CO2 emissions in Sub-Saharan African countries - Tijjani, Babuga Umar (2021)
This study is aimed at achieving three goals, firstly, to examine the long run relationship between the oil price change and economic growth for Sub-Saharan Africa (SSA) net oil exporters with the aim of finding the threshold level where an increase beyond that is no longer or even contributing negatively to the economic growth of these countries. The existence of cross-sectional dependence on the panel data of these countries is what prompted for the application of second-generation panel technique, Augmented Mean Group (AMG) method as proposed by (Eberhardt & Bond, 2009; Eberhardt & Teal, 2010). The findings indicates that, oil price increase has stimulated the economic growth up to a certain level, then further increase in the price of oil beyond that is leading to negative economic growth. Therefore, the study concludes that a threshold level exists for oil price-economic growth of the SSA net exporters, Angola and Nigeria are the countries that are found to fall below the threshold level while Cameroon, Congo DR, Congo Republic, Equatorial Guinea and Gabon were the countries that are found to be above the threshold level. These countries should adopt policy measures to promote and diversify other economic sectors that are non-oil tradable so that countries that are above the threshold level can reduce the negative effect of the oil price increase on their economic growth. Thus, for those that fall below the threshold, diversification to other non-oil economic activities can prevent the occurrence of negative effect of oil price on their economic growth. The second objective is aimed at investigating the long run effect of oil price change on inflation for the SSA countries. Similarly, the presence of cross-sectional dependence among the panel data units is what necessitated for the application of the secondgeneration panel technique, (AMG) method as proposed by (Eberhardt & Bond, 2009; Eberhardt & Teal, 2010). The findings show that oil price changes had positively affected the price level, as oil price goes up the rate of inflation is also rising. For policy measure, the governments in these countries should adopt policy measures of reducing inflation by cutting the importation level and promoting the indigenous domestic manufacture to be producing different consumer goods so that they can meet up with the rising domestic demand. The third objective is aimed at examining the long run relationship among the energy consumption and CO2 emissions at both aggregate and disaggregate levels for the SSA countries. The study utilized a second-generation econometric panel technique AMG (Eberhardt & Bond, 2009; Eberhardt & Teal, 2010) due to the presence of crosssectional dependence on the panel data. Applying of first-generation panel technique in the event of cross-sectional dependence on the panel can lead to invalid and inconsistent results. The findings indicate that energy consumption at both aggregate and disaggregate level has positively affected the CO2 emission. As consumption of energy increases, the rate of environmental pollution through the CO2 emission also increases. For policy implication, some of the ways to cut down the rate of CO2 emission from consumption of energy is by promoting and making the renewable energy sector attractive to investment so that efforts could be made in providing cleaner and efficient energy sources such as solar, wind and et cetera that are not harmful to the environment.